Tanggapan Masyarakat terhadap Layanan di Perpustakaan Masjid Ummi Nagari Alahan Panjang Kabupaten Solok - Lenia, Pramise; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThis paper discusses the community's response to the services in the ummi nagari mosque in Alahan Panjang, Kabupaten Solok. The purpose of this study was to describe the community's response to the services at the Ummi Nagari Alahan Panjang Mosque Library Kabupaten Solok. The method used is descriptive method with a quantitative approach, which is collecting data directly and distributing questionnaires at the Ummi Nagari Alahan Panjang Mosque Library Kabupaten Solok. Based on analyzing the data, it can be concluded as follows. First, the community's response to librarians is good, because the services provided by librarians make people very satisfied. Second, the community's response to collections in the library is good, because the collections provided in the library are complete. Third, the community's response to the facilities is also good, this can be seen from the people who visit the library, they feel comfortable with the facilities provided.Keyword:Â  services, library.